Addressing burn-injury stigma through health education and communication campaign in Pakistan: study protocol - Eylem-van Bergeijk, Özlem; Hussain, Ali; Panagioti, Maria; Khoso, Ameer B.; Zadeh, Zainab F.; Rehan, Muhammad; Kiran, Tayyeba; Hodkinson, Alexander; Wang, Duolao; Blakemore, Amy; Brooks, Helen; Iqbal, Tariq; et al. (Frontiers in Public Health, 2025)
BackgroundBurn injuries remain a neglected public health issue in low-and middle-income countries (LMICs). Up to 90% of burn injuries occur in LMICs, where there is a lack of appropriate burn prevention, acute care and rehabilitation services. When co-created with target populations, health education and communication campaigns could play a pivotal role in promoting risk assessment and improving knowledge, attitudes and practices regarding first aid for burns in low-resource settings. Photovoice is a co-creation approach that engages target communities in capturing and communicating their lived experiences through photography. The present study protocol describes the design of a health education and communication campaign incorporating Photovoice to improve knowledge, attitudes and practices regarding burn injuries in Pakistan.Methods and analysisThis cohort study will follow 600 participants (n = 600; n = 500 burn survivors; n = 100 caregivers) with three measurement points at 6- to 12-month intervals. The primary outcomes are knowledge, attitudes and practices regarding burn injuries. The secondary outcomes are meaning in life; gratitude, resentment and appreciation; hope; optimism; temporal satisfaction with life; coping strategies; social interaction anxiety; self-stigma and resilience, measured using the Meaning in Life Questionnaire, the Gratitude, Resentment and Appreciation Scale, the Adult Workers Hope Scale, the Patient Optimism Scale, the Temporal Satisfaction with Life Scale, the COPE Inventory, the Social Interaction Anxiety Scale, the Self-Stigma Scale and the Brief Resiliency Scale, respectively. The participants are grouped as follows: the exposure group (i.e., burn survivors [n = 200] and caregivers [n = 100] exposed to campaign messages), the non-exposure group (i.e., burn survivors [n = 250] not exposed to campaign messages) and the Photovoice group (i.e., burn survivors [n = 50] who participate in Photovoice and are exposed to the campaign messages). This design evaluates the impact of the health communication campaign and determines whether Photovoice has any additional effects on the primary and secondary outcomes.Ethics and disseminationEthical approval was obtained from the Pakistan National Bioethics (Approval ID: NBC-985) and Manchester University Research Ethics Committees (Approval ID: 2023-18,027-31199). The results of this study will be distributed through public dissemination events, social media channels and peer-reviewed journals.